2007
DOI: 10.1038/sj.ejcn.1602631
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation with flaxseed oil lowers blood pressure in dyslipidaemic patients

Abstract: Objective: Alpha-linolenic acid (ALA) is the natural precursor of the cardioprotective long-chain nÀ3 fatty acids. Available data indicate a possible beneficial effect of ALA on cardiovascular disease (CVD), but the response of various CVD risk factors to increased ALA intake is not well characterized. The purpose of the present study was to examine the effect of increased ALA intake on blood pressure in man. Design, setting, subjects and interventions: We used a prospective, two-group, parallel-arm design to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
76
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(82 citation statements)
references
References 31 publications
5
76
0
1
Order By: Relevance
“…SDG reduced the angiotensin I-induced rise in the arterial pressures and hence SDG was a potent Angiotensin-Converting Enzyme (ACE) inhibitor (Paschos et al, 2007;Prasad, 2009). And SDG supplementation could protect against the development of chronic diseases, cancer and diabetes on animal studies using various models of rat, mice and rabbit (Adolphe et al, 2010).…”
Section: The Statistical Analysismentioning
confidence: 99%
“…SDG reduced the angiotensin I-induced rise in the arterial pressures and hence SDG was a potent Angiotensin-Converting Enzyme (ACE) inhibitor (Paschos et al, 2007;Prasad, 2009). And SDG supplementation could protect against the development of chronic diseases, cancer and diabetes on animal studies using various models of rat, mice and rabbit (Adolphe et al, 2010).…”
Section: The Statistical Analysismentioning
confidence: 99%
“…Many studies have shown its positive effects when used as a supplemental feeding. These effects are manifested as improvement in lipid profile 12 , reducing the development of type 1 and type 2 diabetes mellitus 13 , reducing blood pressure 14 , and controlling weight gain 15 .…”
Section: Introductionmentioning
confidence: 99%
“…ALA as an antihypertensive agent has been studied in a limited number of studies,63 and the lack of effect on blood pressure with ALA is at odds with previous clinical studies that demonstrate the hypotensive effects of ALA in hypertensive individuals 56. Mice, however, are deficient in the enzyme that is responsible for the endogenous metabolism of ALA64 and thus may respond differently to ALA than humans.…”
Section: Discussionmentioning
confidence: 99%